3D Oxygen‐Defective Potassium Vanadate/Carbon Nanoribbon Networks as High‐Performance Cathodes for Aqueous Zinc‐Ion Batteries. Issue 1 (16th October 2019) - Yang, Wang; Dong, Liubing; Yang, Wu; Xu, Chengjun; Shao, Guangjie; Wang, Guoxiu
Abstract: Rechargeable aqueous zinc‐ion batteries (ZIBs) have attracted extensive interest owing to their low cost and high safety. Herein, oxygen‐defective potassium vanadate/amorphous carbon nanoribbons (C‐KVO|Od ) are successfully synthesized through a one‐step solid‐state sintering process as a high‐performance cathode material for ZIBs. This unique 3D interconnected network structure can not only act as a continuous conductive path but also decrease aggregation and provide more adsorption sites for zinc ions. The as‐prepared C‐KVO|Od exhibits a high capacity of 385 mAh g −1 at 0.2 A g −1, superior rate performance (166 mAh g −1 even at 20 A g −1 ), and an outstanding cycling stability with a 95% capacity retention over 1000 cycles. Density functional theory calculations elucidate that the oxygen defects in the C‐KVO|Od remarkably reduce the Zn 2+ ion's adsorption Gibbs free energy and Zn 2+ ‐diffusion barriers. Meanwhile, the amorphous carbon networks enable the rapid electron transfer and provide additional active sites for Zn 2+ storage. This work can facilitate the development of high‐performance ZIBs for large‐scale energy storage. Abstract : A 3D interconnected oxygen‐defective potassium vanadate embedded with amorphous carbon network is rationally designed and synthesized by a one‐step solid‐state sintering method. When applied as cathode materials for aqueous zinc‐ion batteries, the carbon acts as a continuous conductive network, while oxygen defects in potassium vanadate can greatly decrease the Zn 2+ diffusion barrier and enable much faster reaction kinetics.